A novel therapeutic approach for LPIN1 mutation–associated rhabdomyolysis—The Austrian experience. Issue 3 (24th July 2015) - Pichler, Karin; Scholl‐Buergi, Sabine; Birnbacher, Robert; Freilinger, Michael; Straub, Simon; Brunner, Jürgen; Zschocke, Johannes; Bittner, Reginald E.; Karall, Daniela
ABSTRACT Introduction: Lipin 1 gene (LPIN1) mutations lead to cellular energy deficiency and cause up to 50% of the rhabdomyolysis episodes seen in pediatric patients. These episodes are associated with poor prognosis, as treatment options have been limited. We propose a novel therapeutic strategy based on prevention and early treatment of catabolism. Methods: Five patients were diagnosed with LPIN1 mutations. They were instructed to maintain high caloric intake in situations possibly leading to catabolism such as viral infections or excessive physical activity. When an episode of rhabdomyolysis occurred, patients were treated with intravenous high‐concentration glucose at first symptoms. Results: The therapeutic strategies described limited the number of rhabdomyolyis episodes, and the duration of episodes was reduced from 7–10 days, as reported in the literature, to 5 days. Conclusion: In this small series, patients with LPIN1 mutations appear to have benefited from prevention and early treatment of catabolism. Muscle Nerve 52:437–439, 2015